Electrochemical Flash Fluorination and Radiofluorination. Issue 22 (30th August 2018) - Balandeh, Mehrdad; Rios, Alejandra; Allison, Nathanael; Shirazi, Daniela; Gomez, Adrian; Rambaran, Laura; Holloway, Travis; Sadeghi, Saman
Abstract: A new method for rapid late‐stage fluorination using the cation pool technique is presented. Fluorination and no‐carrier‐added radiofluorination of methyl (phenylthio) acetate, methyl 2‐(methylthio) acetate, and methyl 2‐(ethylthio) acetate were performed. The carbocations formed through electrochemical oxidation were stabilized by using a divided electrochemical cell and 2, 2, 2‐trifluoroethanol (TFE) as the solvent at −20 °C. At the end of electrolysis, either stable‐isotope [ 19 F]fluoride or no‐carrier‐added radioactive [ 18 F]fluoride was added to the reaction mixture to form the fluorinated or radiofluorinated product. Abstract : Radio‐labelling using cation pool : Successful electrochemical fluorination and radiofluorination using the cation pool technique is reported. This method provides a truly late‐stage fluorination reaction, maximizing radiochemical yield by minimizing decay through a rapid reaction of the previously prepared cations with [ 18 F] fluoride.